Prevalence of impairments, disabilities, handicaps and quality of life in the general population: a review of recent literature - Barbotte Eric; Guillemin Francis; Chau Nearkasen (The World Health Organization, 2001)
OBJECTIVE: To determine the prevalence rates of morbidity in the general population through bibliographic research. METHODS: Articles relating to impairment, disability, handicap, quality of life and their prevalence in the general population, published between January 1990 and March 1998, were selected on the MEDLINE database. FINDINGS: The 20 articles retained out of 433 used 41 different indicators. Indicators of impairment, disability, handicap and low quality of life showed prevalence rates of 0.1-92%, 3.6-66%, 0.6-56% and 1.8-26% respectively, depending on age and the accuracy of indicators. The heterogeneity of the conceptual framework and insufficient recognition of the importance of indicator accuracy, the age factor and the socioeconomic characteristics of the studied populations impede reliable international comparison. CONCLUSION: Further standardization of indicators is therefore required. The revision of the International Classification of Impairments, Disabilities and Handicaps may make it possible to resolve some of the difficulties encountered.